Augmented cognition : theoretical and technological approaches : 14th International Conference, AC 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: theoretical and technological approaches : 14th International Conference, AC 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available